I have struggled a while with this one. I dont understand how it comes like this, from the beginning I have R2/(R2+R1+(1/x)) → (x*R2)/(1+x(R2+R1)) if someone can show me how it can change i will be very glad.
It can't - plug in some real values for R1, R2 and x and you'll find the two forms are different. e.g. let x=5, R1=2 & R2= 3 R2/(R1+R2+x)=3/10 but x*R2/(1+x(R1+R2))=5*3/(1+25)=15/26
R2/(r2+r1+(1/x)) just take the lcm of denominator which is x in this case now r2/(r2*x+r1*x+1)/x r2*(x)/(1+x(r1+r2)) r2x/(1+x(r1+r2)) thats all